Revealing G‐protein‐coupled receptor oligomerization at the single‐molecule level through a nanoscopic lens: methods, dynamics and biological function. (28th November 2015) - Scarselli, Marco; Annibale, Paolo; McCormick, Peter J.; Kolachalam, Shivakumar; Aringhieri, Stefano; Radenovic, Aleksandra; Corsini, Giovanni U.; Maggio, Roberto
Abstract : The introduction of super‐resolution fluorescence microscopy has allowed the visualization of single proteins in their biological environment. Recently, these techniques have been applied to determine the organization of class A G‐protein‐coupled receptors (GPCRs), and to determine whether they exist as monomers, dimers and/or higher‐order oligomers. On this subject, this review highlights recent evidence from photoactivated localization microscopy (PALM), which allows the visualization of single molecules in dense samples, and single‐molecule tracking (SMT), which determines how GPCRs move and interact in living cells in the presence of different ligands. PALM has demonstrated that GPCR oligomerization depends on the receptor subtype, the cell type, the actin cytoskeleton, and other proteins. Conversely, SMT has revealed the transient dynamics of dimer formation, whereby receptors show a monomer–dimer equilibrium characterized by rapid association and dissociation. At steady state, depending on the subtype, approximately 30–50% of receptors are part of dimeric complexes. Notably, the existence of many GPCR dimers/oligomers is also supported by well‐known techniques, such as resonance energy transfer methodologies, and by approaches that exploit fluorescence fluctuations, such as fluorescence correlation spectroscopy (FCS). Future research using single‐molecule methods will deepen our knowledge related to the function and druggability of homo‐oligomers and hetero‐oligomers. Abstract : The introduction of super resolution fluorescence microscopy has allowed to visualize single proteins in their biological environment. This review highlights recent evidence coming from Photoactivated Localization Microscopy (PALM) and Single‐Molecule Tracking (SMT) applied to study the plasma membrane organization of some G protein‐coupled receptors (GPCRs). GPCRs form transient dimers and/or oligomers depending from receptor subtype, cell‐type, actin cytoskeleton and other proteins.